Knowledge and behaviour assessment of drivers and community people towards road safety: A baseline study - Samadder, Mrinmoy; Saha, Polin Kumar (BRAC Research and Evaluation Division, 2022)
Recently, road traffic accidents are considered to be the leading cause of death both in developed and developing countries. In Bangladesh, BRAC has recently initiated a new program on road safety in aiming to increase road safety awareness among road users. The ultimate goal of the program is to achieve “zero fatal road accidents” between Syedpur- Enayetganj road of Nabiganj Upazila in Habiganj district. The study intends to understand the current status of knowledge and practices on road safety of selected motor and non-motor drivers, students, teachers and a group named Community Road Safety Group (CRSG). To achieve this goal, the present study conducts conducted a baseline survey in both intervention and control areas followed by Focus Group Discussion (FGD), in-depth interviews, and investing the CRSG group formation including its activity plan in the treatment area. Findings show that both the drivers and students possess poor knowledge about the traffic rules and the road safety issue. Alternatively, it is also found a significant issue that there is a huge gap between knowledge and behaviour of drivers at time of driving. Finally, it has been revealed that road accidents blame to many contributory factors leading to site-specific road accidents such as a variety of vehicles in a specific road structure, speed of the vehicles, traffic regulations, poor education of students etc. and all of these are interrelated with the human attitude, behaviour and road conditions.